Stress A-Z : a sourcebook for facing everyday challenges - Kahn, Ada P. (New York : Facts on File, 1998)
Contains over five hundred alphabetically arranged entries that provide information about the causes, effects, and treatments of physical and physiologic stress.
Includes bibliographical references (p. 365-378) and index.
Library Journal.
Adult
Keywords: Stress (Physiology) -- Encyclopedias; Stress (Psychology) -- Encyclopedias; Stress (Physiology) -- Encyclopedias; Stress (Psychology) -- Encyclopedias